LAR-SiCo: recommending law articles based on multi-label text classification - Zhao, Hua; Li, Xiaoqian; Zeng, Qingtian; Zou, Zhenqi; Liang, Jinguo (International journal of machine learning and cybernetics, 2025)
How to automatically recommend the law articles violated by the illegal advertisements is one of the hot topics in the smart justice. Because an illegal advertisement may violate one or more law articles, we proposed to consider the automatic recommendation of law articles as a multi-label text classification (MLTC) task, and created a law article recommendation method based on multi-label text classification. To address the issue of insufficient labeled data in the field of illegal advertisement, a law article recommendation method based on label semantic information and label co-occurrence (LAR-SiCo) was proposed. LAR-SiCo firstly used the BERT to obtain the initial law article vector; secondly, based on Node2Vec and Graph convolution Network (GCN), the initial law article vector was updated iteratively by utilizing law article semantic information and law article co-occurrence, which was optimized using the proposed label loss. Finally, the classification loss and label loss were combined to optimize LAR- SiCo. At the same time, we constructed an illegal advertisement dataset for law articles recommendation. The experimental results showed that LAR-SiCo was feasible and effective in recommending the law articles violated by the illegal advertisements.